PENGARUH TATA KELOLA TERHADAP PRAKTIK EKSPROPRIASI DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL PEMODERASI - Dewi Diah Fakhriyyah; Bambang Purnomosidhi; Imam Subekti (Universitas Mercu Buana, 2017)
Abstract. The concentrated ownership structure that occurred in Indonesia led to theagency conflicts between the controlling shareholder and the non-controllingshareholder will lead expropriation. This study aims to examine the effect ofgovernance on expropriation practices. In addition, the study also aims to examine themoderation role of dividend policy in strengthening the governance effect onexpropriation practices. The results show that governance negatively affects thepractice of expropriation and dividend policy can not strengthen the negative effect ofgovernance on the practice of expropriation. This study contributes to the theory ofagency type II which discusses conflicts between controlling and non-controllingshareholders, which can be overcome by the use of corporate governance mechanisms Keywords: governance, expropriation, dividend policy, related party transaction